(3GdGfJUGQ Ydi YdeGA GdCeUGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3jHOC HGdaUd GdKGdK ai GdHjfGJ s
(3BNQgG (B:s
(3jfJgi CKfGA HGH GdMhGdI , ai GdcdGe Ydi GdMce GdNGeS s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ , JGeI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis